Features of remodeling of right heart chambers according to tissue Doppler and its correlation with cardiac rhythm disturbance in patients with COPD 2-3 severity - O. A. Zhuk; V. E. Perley; A. Y. Gichkin; A. L. Alexandrov; O. N. Titova; N. A. Kuzubova; N. V. Egorova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article presents the study of early sings of dysfunction of right and left chambers of heart in patients with COPD 2 - 3 severity, correlation between structural and electrical remodeling of heart according to the stages of pulmonary hypertension. Standard tissue Doppler echocardiographic parameters and modes were used for the diagnosing. We examined 35 patients with COPD 2 - 3 severity; the control group consisted of 15 patients. The ECG Holter monitoring was made for all patients to identify cardiac rhythm disturbance and correlation with the COPD severity. Standard method of the ECG with modes of tissue Doppler (pulsed wave Tissue Doppler Imaging - PW TDI, color tissue Doppler imaging -TDI, tissue myocardial Doppler - TMD, tissue Tracking - TT, Doppler for evaluation of myocardial strain and myocardial strain rate) were made to identify the stage of dysfunction. The results of the study concluded that according to the TDI the dysfunction of right ventricle was more apparent in patients with COPD 3 severity. Pathological arrhythmias were significantly detected in group of patients with COPD 3 severity. In compliance with our observations, the reduce of rapid myocardial strain rates and its inverse proportion with the severity in accordance to the evaluation of longitudinal strain and rate of movement of fibrous ring in tricuspid valve were observed in patients with COPD. Thus the application of the TDI modes for evaluating of early signs of cardiac remodeling in patients with COPD and potential adequate jugulation for preventing chronic cor pulmonale is expedient.